The relation between Schneiderian membrane thickening and radiodiagnostic features of periapical pathology - Oliveira-Santos, Nicolly; Leite, André Ferreira; Petitjean, Eline; Torres, Andres; Van der Veken, Dominique; Curvers, Frederik; Pinto, Jáder Camilo [UNESP]; Lambrechts, Paul; Jacobs, Renhilde (FapUNIFESP (SciELO), 2024)
This study aimed to assess the relationship between Schneiderian membrane thickening and periapical pathology in a retrospective analysis of Cone Beam Computed Tomography (CBCT) images. For this, 147 CBCT scans containing 258 sinuses and 1,181 teeth were assessed. Discontinuation of the lamina dura, widening of the periodontal ligament space, apical periodontitis (AP), and partly demineralized maxillary sinus floor associated with AP were considered periapical pathology. Maxillary sinus mucosal thickening (MSMT) was classified as odontogenic or non-odontogenic. An irregular band with a focal tooth associated thickening and local thickening related to a root were considered odontogenic types of MSMT. The relation between the imaging features of periapical pathology and the type and thickness of MSMT was determined by logistic regression and linear mixed model, respectively. In addition, linear regression and Mann Whitney test evaluated the relation and demineralization of the AP lesion towards the sinus floor (p≤0.05). The odds of having an odontogenic type of MSMT were significantly higher when a periapical pathology was present in the maxillary sinus. Eighty-two percent of AP partly demineralized towards the sinus floor were associated with an odontogenic MSMT. Both AP lesions partly demineralized towards the sinus floor and, with increased diameter, led to increased MSMT. In conclusion, there is an 82% risk of having an odontogenic type of MSMT with the presence of AP partly demineralized towards the sinus floor. More thickening of the maxillary sinus mucosa is seen with larger AP lesions and partial demineralization of the sinus floor.
Keywords: apical periodontitis; cone-beam computed tomography; maxillary sinus; Schneiderian membrane